Extending the game immersion questionnaire to online users - Dombrovskis, Valērijs; Ļevina, Jeļena; Ruža, Aleksejs (Frontiers in Psychology, 2025)
IntroductionThe Game Immersion Questionnaire (GIQ) serves as a tool for evaluating immersion within the realm of online gaming. Immersion is a crucial psychological state experienced by users interacting with digital environments, influencing their engagement, engrossment, and total involvement. While the original GIQ was structured around seven first-order factors and three second-order factors, its applicability beyond gaming contexts remains unexplored. This study extends the GIQ to capture the immersion experiences of a more expansive cohort of online users beyond gamers.MethodsThe extended GIQ was administered to a cohort of active internet users from Latvia (n = 227), aged 13 to 65 (M = 26.6, SD = 8.4), with 53.7% identifying as female, 33% as male, and 13.2% as nonbinary. Factor analysis was conducted to examine the structure of the extended questionnaire and validate its applicability to a broader range of online users.ResultsFactor analysis revealed three first-order factors – Engagement, Engrossment, and Total Immersion – that together form a global second-order factor named the Level of Immersion in the Digital Environment. These findings align with the original hierarchical structure of the GIQ while extending its relevance to a wider population of online users.DiscussionThe extended GIQ provides insights into the immersion experiences of a diverse range of online users across various digital environments. By adapting the GIQ for broader use, this study contributes to the understanding of immersion beyond gaming and supports its application in different online contexts.